IMPLEMENTATION OF HIGHER ORDER THINKING SKILLS (HOTS)-BASED EDUCATION TO ENHANCE THE QUALITY OF ENGLISH LANGUAGE FOR STUDENTS AT SDN 1 TIMPAG - Utik Kuntariati; Putu Dian Yuliani Paramita; Gede Eka Wahyu (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
Quality of education 4.0 is aimed at producing competent and quality human resources in carrying out activities in the industrial world later ( Pohan , 2019). In the current implementation of education in capturing information on the resulting human resources, it is required to obtain information on a very broad scale and human resources are also required to be able to understand various matters, one of which is understanding related to English. In this study, the researcher used a qualitative descriptive method to describe the HOTS concept which would be implemented in English learning activities at SDN 1 Timpag . Qualitative research generally describes the dominant data using words rather than describing phenomena through a numeric number. Based on the results of the research that has been done, some conclusions that can be drawn in this study are that the HOTS indicator learning method is developed in its entirety, there are 6 indicators including Creating, Evaluating, Analyzing, Applying, Remembering and Understanding . At SDN 1 Timpag as a whole there are several implementation indicator ideas that can be improved in the implementation of HOTS in English materials including story telling planning, introduction to animal objects and body anatomy and simple greetings and the use of grammar.